2018
DOI: 10.1111/jnc.14288
|View full text |Cite
|
Sign up to set email alerts
|

Validated multi‐step approach for in vivo recording and analysis of optogenetically evoked glutamate in the mouse globus pallidus

Abstract: Precise quantification of extracellular glutamate concentrations upon neuronal activation is crucial for the understanding of brain function and neurological disorders. While optogenetics is an outstanding method for the correlation between distinct neurons and their role in circuitry and behavior, the electrochemically inactive nature of glutamate has proven challenging for recording upon optogenetic stimulations. This difficulty is due to the necessity for using enzyme-coated microelectrodes and the risk for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…The STN is the only glutamatergic nucleus in the BG, and it represents the main excitatory input to GP neurons (Kita and Kitaï, 1987;Smith et al, 1990). It has been shown in mice that optogenetic activation of STN axon terminals within the GP increases glutamate release (Viereckel et al, 2018) and c-Fos expression (Tian et al, 2018). We show here that, similar to D2-SPN inputs, STN inputs differentially impact the activity of prototypic and arkypallidal neurons.…”
Section: Stn Inputs Cause a Disynaptic Inhibition In Arkypallidal Neumentioning
confidence: 52%
“…The STN is the only glutamatergic nucleus in the BG, and it represents the main excitatory input to GP neurons (Kita and Kitaï, 1987;Smith et al, 1990). It has been shown in mice that optogenetic activation of STN axon terminals within the GP increases glutamate release (Viereckel et al, 2018) and c-Fos expression (Tian et al, 2018). We show here that, similar to D2-SPN inputs, STN inputs differentially impact the activity of prototypic and arkypallidal neurons.…”
Section: Stn Inputs Cause a Disynaptic Inhibition In Arkypallidal Neumentioning
confidence: 52%
“…The Pitx2 gene encodes a transcription factor essential for STN development and function [26][27][28] . We recently verified that expression of the optogenetic ion channel Channelrhodopsin (ChR2) in the STN of Pitx2-Cre mice causes post-synaptic currents and glutamate release in STN target areas upon photostimulation 24,25 , thus validating the use of optogenetics in Pitx2-Cre mice for the study of STN.…”
Section: Expression Of Optogenetic Constructs In the Stn Of Pitx2-crementioning
confidence: 88%
“…By implementing optogenetics, new possibilities to directly compare the behavioral readout upon STN excitation and inhibition has opened up. Based on our previous data showing that 20 Hz photostimulation was sufficient to release glutamate in the GP of Pitx2/ChR2 mice 25 , a photoexcitation protocol designed for behavioral motor analysis was formulated. We found that GP neurons were excited already upon a 0. the open field test, immediate self-grooming was initiated upon STN excitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations